La,N-codoped TiO2 Visible-Light Responsive Photocatalysts Prepared by Hydrolysis Precipitation Method - Zhang*, Xiang-Lin; Wang, Zheng-An; Luo, Zhuyi; Liu, Xueting (Asian Journal of Chemistry, 2011)
La,N-codoped TiO2 photocatalysts were synthesized via hydrolysis precipitation method and characterized by X-ray diffraction, X-ray photoelectron spectra and UV-vis diffuse reflectance spectra. The photocatalytic activity of the as-prepared samples under visible light irradiation was tested using methylene blue as a model organic pollutant. The results indicate that nitrogen and lanthanum ions are incorporated into the interstices of anatase titania nanocrystals, which induces the expected red-shift of absorption band edge, the suppression of the recombination of photo-induced electron-hole pairs and the enhanced photocatalytic activity under visible light irradiation. When N:La:Ti molar ratio is at 0.02:0.003:1, the photocatalytic activity of the codoped samples is the highest, which is about three times as high as that of pure titanium dioxide.